2019
DOI: 10.1111/trf.15446
|View full text |Cite
|
Sign up to set email alerts
|

Stored platelet number and viscoelastic maximum amplitude are not altered by warming or rapid infusion

Abstract: BACKGROUND Platelet transfusion is an important aspect of hemostatic resuscitation. Leading textbooks recommend never infusing platelets through warmers or rapid infusers, but there is no evidence to justify this position. MATERIALS AND METHODS We obtained units of apheresis platelets in plasma from our hospital blood bank and drew a baseline sample from every unit. In the warmer arm, an aliquot from each unit was injected into a fluid warmer heated to 41°C (Ranger, 3M Corporation). After 5 minutes' incubation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…They found a significant reduction in platelet count at 70 mL/min and 100 mL/min and differences in thrombin generation, but no reduction in the MA on TEG. Hess et al [ 14 ] performed 10 iterations of infusing platelets stored in plasma through a Belmont RI-2 and samples were evaluated using platelet count and TEG. They did not find any significant differences between pre-infusate and post-infusate.…”
Section: Discussionmentioning
confidence: 99%
“…They found a significant reduction in platelet count at 70 mL/min and 100 mL/min and differences in thrombin generation, but no reduction in the MA on TEG. Hess et al [ 14 ] performed 10 iterations of infusing platelets stored in plasma through a Belmont RI-2 and samples were evaluated using platelet count and TEG. They did not find any significant differences between pre-infusate and post-infusate.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we intent to monitor the hemolytic rate before and after unwarmed and warmed transfusions using the sensitive metric of end-tidal carbon monoxide. 17 Platelets could potentially be damaged by an inline warmer, but Hess et al 18 found no adverse effect of a warmer on PLT count or PLT function, using an in vitro simulation of adult-type transfusions. Similarly, we found no evidence of PLT damage using our NICU transfusion simulation.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid infusion was studied using a 300 mm Hg pressure bag and was not shown to reduce aggregation. Hess and colleagues 8 infused (n = 10) 5‐ to 7‐day‐old apheresis PLT units through a Ranger blood warming device and found no decease in PLT count and TEG MA as a measure of PLT function. Rapid infusion of apheresis PLT units at 500 mL/min via a rapid infusion system (Belmont) also did not reduce PLT count or TEG MA.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these guidelines, many anesthesia providers infuse PLT transfusions through warming devices in supplementary efforts to prevent perioperative hypothermia and its harsh complications 3,6 . There are now three small (each study n = 10) in vitro studies that show infusion of PLT units through blood warmers does not impair PLT function 6–8 …”
mentioning
confidence: 99%